PENGARUH PREDISPOSISI, ENABLING DAN REINFORCING TERHADAP UTILITAS POS PEMBINAAN TERPADU PENYAKIT TIDAK MENULAR - Evi Fitriani Nasution; Kiki Putri Anriani Hutabarat (Jurnal Penelitian Kesmasy, 2018)
Non-Communicable Disease Integrated Development Post is manifestation of community participation in the activities of early detection, monitoring and action continued early PTM risk factors independently and continuously. This activity developed as a form of early awareness of PTM, remembering almost most PTM in the early stages are asymptomatic that are significant This study aims to analyze the influence of predisposing, enabling and reinforcing factors on Utilities for Integrated Coaching of Non-Communicable Diseases at the Danau Marsabut Health Center, Sipirok District, South Tapanuli Regency. This type of research is analytic with cross sectional research design. The population in this study were all PTM targets in PTM Posbindu totaling 3670 people from January to May 2018. The sample was 95 people with purposive sampling method. Data were analyzed by univariate, bivariate and logistic regression. The results showed that those who used Non-Communicable Disease Integrated Development Post were 64 people (67.4%) and 31 people (32.6%) who did not use it. There is the influence of knowledge (p value 0.001), attitude (p value 0.001), distance (p value 0.041), transportation (p value 0.001), family support (p value 0.004), and officer attitudes (p value 0.014) to the utility of Non-Communicable Disease Integrated Development Post. The most influential variable on the utility is knowledge. It is recommended to the South Tapanuli District Health Office to monitor, controlling and evaluating the implementation of Non-Communicable Disease Integrated Development Post services in each Technical Implementation Unit (TIU) and hospitals in South Tapanuli Regency.